2012
DOI: 10.1111/j.1750-3841.2012.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Antioxidants in Some Vigna Species of Legumes and their Distinct Inhibitory Effects on α‐Glucosidase and Pancreatic Lipase Activities

Abstract: Phenolic extracts of 4 Vigna species of legumes (mung bean, moth bean, and black and red varieties of adzuki beans) were evaluated for phenolic contents, antioxidant activities, and inhibitory properties against α‐glucosidase and pancreatic lipase. Results showed that adzuki bean varieties contain higher phenolic indexes than mung bean and moth beans. Adzuki bean (black) variety was found to be the most active 2,2´‐diphenyl‐1‐picrylhydrazyl and superoxide anion scavenger. However, the hydrogen peroxide scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 34 publications
2
63
4
3
Order By: Relevance
“…Obesity is primarily caused by the disorder of lipid metabolism, and lipase inhibitors can inhibit the absorption of dietary triglyceride to prevent obesity [12,13]. Since most herbal plants exhibit multiple pharmaceutical effects through multiple targets [14,15], it is of great interest to find out if S. baicalensis contains lipase inhibitors in addition to α-glucosidase inhibitors. To the best of our knowledge, no relevant studies have been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is primarily caused by the disorder of lipid metabolism, and lipase inhibitors can inhibit the absorption of dietary triglyceride to prevent obesity [12,13]. Since most herbal plants exhibit multiple pharmaceutical effects through multiple targets [14,15], it is of great interest to find out if S. baicalensis contains lipase inhibitors in addition to α-glucosidase inhibitors. To the best of our knowledge, no relevant studies have been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that total phenolics extracted from mung bean inhibited 17.7% of pancreatic lipase activity, and that from adzuki bean inhibited 9.85% of pancreatic lipase activity. [22] The reasons for the different data from the authors' may owe to the different extraction methods.…”
Section: Effects Of 13 Food Legumes On Pancreatic Lipase Activitymentioning
confidence: 97%
“…Reflux extraction at 55℃ with 80% aqueous methanol containing 1% HCl (1:50, w/v) was used to extract for 1 hr by Sreerama et al [22] The extraction time was too short and the post-treatment was omitted, which might affect their inhibitory effects against pancreatic lipase activity.…”
Section: Effects Of 13 Food Legumes On Pancreatic Lipase Activitymentioning
confidence: 99%
“…Determination of antioxidant activity 2.9.1. Total antioxidant activity Total phenolics from defatted millets fractions were extracted according to the method of Sreerama, Takahashi, and Yamaki (2012). Samples were extracted with 80% aqueous methanol containing 1% HCl (1:50, w/v) under reflux in a water bath at 55 C for 1 h. The suspension was centrifuged and extraction was repeated 2 more times.…”
Section: Total Carotenoidsmentioning
confidence: 99%